Queering Black Atlantic Religions: Transcorporeality in Candomblé, Santería, and Vodou - Strongman, Roberto (Religious Cultures of African and African Diaspora People Ser., 2019)
Roberto Strongman examines three Afro-diasporic religions--Hatian Vodou, Cuban Lucumí/Santería, and Brazilian Candomblé--to demonstrate how the commingling of humans and the divine during trance possession produce subjectivities whose genders are unconstrained by biological sex.